Case Report: 100-year-old COVID-positive Hip Fracture Patient for Hemiarthroplasty Under Spinal Anesthesia. (September 2020) - Beathe, Jonathan C.; Memtsoudis, Stavros G.
Elderly patients undergoing hip fracture surgery represent a myriad of perioperative challenges and risks. The arrival of the global pandemic of novel coronavirus disease 2019 (COVID-19) adds an unprecedented challenge to the management of hip fracture patients. We describe the unique experience and favorable outcome of a 100-year-old COVID-positive hip fracture patient that underwent spinal anesthesia for hemiarthroplasty and subsequent hydroxychloroquine (HCQ) therapy. Multiple factors of varying known benefit may have contributed to our outcome, including preoperative medical consultation and assessment, early surgical intervention, regional anesthesia with little to no sedation, early mobilization and HCQ therapy.